Aplikasi Pengamanan Data Email Menggunakan Algoritma Kriptografi XTEA Berbasis WEB - M. Anif; Siswanto Siswanto; Basuki Hari Prasetyo; Muhammad Fachri; Gunawan Pria Utama (Universitas Budi Luhur, 2020)
PT. Tanabe Indonesia is engaged in manufacturing in the health sector and uses cloud-based email and folder sharing facilities. In this case the company does not have a security system that can secure the contents of e-mail messages. In its implementation, the process of sending email on a network does not rule out being read by irresponsible people, such as intruders. This problem can be solved by creating an Email Data Security Application Using a web-based XTEA (Xtended Tiny Encryption Algorithm) Cryptographic Algorithm, so that email messages are not easily compromised. The application that is built also has additional facilities, namely the login process to be able to access it, so that only certain parties who have access rights can use this application. The programming language used in building this data security application is the web-based PHP programming language. From the test results, the file format will change to .sc format. and after going through the encrypt process it will change to be bigger with the average file size increasing by about 22.221 percent from the original file size before going through the encrypt process. From the test results after going through the decrypt process the average file size change will increase by 77.779% percent (22.221 percent reduction), which is the same as the average in the encrypt process